Cross-Cultural Counseling And Religious Tolerance - Neni Elvira. Z; Firman; Maizatul Mardiana Harun (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2025)
This research aims to explain the concept of cross-cultural counseling and religious tolerance. The research methodology involves review literature study and conceptual analysis, drawing insights from scientific journals, books, and relevant documents on cross-cultural counseling and tolerance religious. The findings suggest that cross-cultural counseling is an important and relevant approach in multicultural societies. Culturally sensitive counselors have extensive knowledge and Culturally responsive skills can create an inclusive and supportive environment counseling environment for clients from diverse cultural backgrounds, facilitates effective problem solving and personal growth. This research highlighting the importance of embracing tolerance and respect differences to foster a peaceful and harmonious society amidst culture and religious diversity. In conclusion, cross-cultural counseling presents a sensitive and comprehensive approach in promoting interfaith tolerance in various communities. With respect differences and the rights of individuals to practice their religious beliefs, society can live mutual respect, harmony the spirit of Pancasila as the basis of the Indonesian state.